The Composition of Continental Shelf and Slope Demersal Fish: The Effects of Depth and Latitude - Wellington, Claire Margaret (Curtin University, 2019)
The distribution and relative abundance of Western Australian shelf and upper slope (<570 m) fish assemblages were assessed over a 16° latitudinal range using Baited Remote Underwater Stereo-Video Systems. I observed distinctive fish assemblages with covariates such as latitude, depth, salinity, current direction and speed, consolidated or unconsolidated bottom and the presence or absence of sponge best explaining the differences. At a smaller spatial scale benthic biota, depth and seabed relief were important covariates.